Market Solution to Environmental Tragedy with Coasean Bargaining, Commons in the Form of Common Property, and International Human Rights Law - Aljosa Noga (Groningen Journal of International Law)
This article argues that common property arrangements are relevant for Coasean bargaining, that commons can be understood as a common property institution suitable for Coasean bargaining, and that international human rights law can support commons and facilitate such bargaining for the sake of attaining a better environment. An environmental tragedy of the commons, regardless if occurring in shared resource domains or in relation to shared resources in other regards, can also be synonymous with general environmental decline. Environmental degradation is, at times, described as the production of negative externalities, i.e. effects produced by the use of a resource which negatively impact other users, the environment, or humanity at large. A traditional solution for such externalities, especially in the context of the tragedy of the commons, is privatisation of resources with private property. Contemporarily, however, private property and privatisation is considered flawed because it fails to remove such externalities which are shared by everyone, and which accumulate into general ruin (such as adverse climate change). Nevertheless, property still lies at the heart of many market solutions to environmental degradation, including solutions such as the Coase theorem, which in turn has also traditionally favoured private property. The answer to the conundrum of what property solution could more aptly allow the market to resolve issues like the tragedy of commons may then reside with the concept of commons. The general improvement of our environment may lie with commons permeated by common property facets and human rights that empower people to protect their environments, and by extension, achieve more sustainability, through Coasean bargaining (negotiation) with emitters on the market, without the direct interference by the State.